Novel pyrrolizines bearing 3,4,5-trimethoxyphenyl moiety: design, synthesis, molecular docking, and biological evaluation as potential multi-target cytotoxic agents - Ahmed M. Shawky; Nashwa A. Ibrahim; Ashraf N. Abdalla; Mohammed A. S. Abourehab; Ahmed M. Gouda (Taylor & Francis Group, 2021)
In the present study, two new series of pyrrolizines bearing 3,4,5-trimethoxyphenyl moiety were designed, synthesised, and evaluated for their cytotoxic activity. The benzamide derivatives 16a-e showed higher cytotoxicity than their corresponding Schiff bases 15a-e. Compounds 16a,b,d also inhibited the growth of MCF-7/ADR cells with IC50 in the range of 0.52-6.26 μM. Interestingly, the new compounds were less cytotoxic against normal MRC-5 cells (IC50=0.155-17.08 μM). Mechanistic studies revealed the ability of compounds 16a,b,d to inhibit tubulin polymerisation and multiple oncogenic kinases. Moreover, compounds 16a,b,d induced preG1 and G2/M cell cycle arrest and early apoptosis in MCF-7 cells. The molecular docking analyses of compounds 16a,b,d into the active site in tubulin, CDK-2, and EGFR proteins revealed higher binding affinities compared to the co-crystallised ligands. These preliminary results suggested that compounds 16a,b,d could serve as promising lead compounds for the future development of new potent anticancer agents.Highlights Two new series of pyrrolizines bearing 3,4,5-trimethoxyphenyl moieties were synthesized. Compounds 16a,b,d displayed the highest cytotoxicity against the three cancer cell lines. Kinase profiling test revealed inhibition of multiple oncogenic kinases by compounds 16a,b,d. Compounds 16a,b,d exhibited weak to moderate inhibition of tubulin-polymerization. Compounds 16a,b,d induced preG1 and G2/M cell cycle arrest and early apoptosis in MCF-7 cells. Docking studies revealed high binding affinities for compounds 16a,b towards tubulin and CDK-2.